The Impact of Cancel Culture on Politics and International Relations - L. V. Deriglazova; A. M. Pogorelskaya (Vestnik MGIMO-Universiteta)
The article aims to reveal particularities of cancel culture in politics and international relations using methods of sociology and conflict theory. Deriving from previous research of cancel culture, authors define cancel culture as non-institutionalized form of social control that is implemented through mass mobilization in social media. After informal pressure the formal punishment could follow against those who break norms or behavior expectations. As a kind of social control cancel culture could contribute to overcoming gap between manifested values and social practices, preserving social order and fighting elitism and inequality. At the same time cancel culture could be used as instrument of unfair competition, political struggle and suppression of opinions. Comparison of cancel culture cases in the USA, United Kingdom and Russia allows to conclude that the scale and effectiveness of collective actions depend on national context, different systems of norms and values and cultural practices to react on violation of values and norms.In politics and international relations cancel culture manifests as an addition to actions of formal political institutions, and it aims to undermine authority and reputation of a politician. It is important that in politics and international relations cancel culture is an instrument of informal control, which follows formal sanctions. Conclusions about the nature of cancel culture as an instrument of politics helps to understand better its functions in regard to attempts to “cancel” Russia. Cancel culture adds to formal sanctions and aims to isolate the country, to undermine its legitimacy as international actor. In regard to Russia the efforts are made to “cancel” it on two levels: formal – by sanctions and informal – via rejection to cooperate coming from various professional communities. In both cases countries and respective communities have their own understanding of norms and acceptable means and tools, and thus cancel culture becomes a toll of collective punishment. International relations lack universal understanding of norms and single center of political power, so that causes selective usage of instruments to impact, and thus cancel culture becomes an instrument of political struggle.